Classical swine fever virus non-structural protein 5B hijacks host METTL14-mediated m6A modification to counteract host antiviral immune response. - Jing Chen; Hui-Xin Song; Jia-Huan Hu; Ji-Shan Bai; Xiao-Han Li; Rui-Cong Sun; Bing-Qian Zhao; Mei-Zhen Li; Bin Zhou (PLoS Pathogens, 2024)
Classical Swine Fever (CSF), caused by the Classical Swine Fever Virus (CSFV), inflicts significant economic losses on the global pig industry. A key factor in the challenge of eradicating this virus is its ability to evade the host's innate immune response, leading to persistent infections. In our study, we elucidate the molecular mechanism through which CSFV exploits m6A modifications to circumvent host immune surveillance, thus facilitating its proliferation. We initially discovered that m6A modifications were elevated both in vivo and in vitro upon CSFV infection, particularly noting an increase in the expression of the methyltransferase METTL14. CSFV non-structural protein 5B was found to hijack HRD1, the E3 ubiquitin ligase for METTL14, preventing METTL14 degradation. MeRIP-seq analysis further revealed that METTL14 specifically targeted and methylated TLRs, notably TLR4. METTL14-mediated regulation of TLR4 degradation, facilitated by YTHDF2, led to the accelerated mRNA decay of TLR4. Consequently, TLR4-mediated NF-κB signaling, a crucial component of the innate immune response, is suppressed by CSFV. Collectively, these data effectively highlight the viral evasion tactics, shedding light on potential antiviral strategies targeting METTL14 to curb CSFV infection.